Enhanced wear resistance, hydrophobic properties and corrosion resistance of plasma electrolyte oxidation coatings on Ti6Al4V alloys via addition of ZrO2 nanoparticles - Yue Yang; Weihua Zhang; Kunlong Zhang; Xiangyu Sun; Boxuan Men; Sirong Yu (Journal of Materials Research and Technology)
Nanocomposite-coatings were fabricated on the Ti6Al4V titanium alloy plates via plasma electrolyte oxidation (PEO) with the addition of ZrO2 nanoparticles (NPs), followed by low surface energy modification. Effects of ZrO2 NPs concentrations on microstructure, adhesive strength, wear resistance, hydrophobic property and corrosion resistance of the PEO coatings were investigated, and corresponding influence mechanisms were revealed. The dual-layered nanocomposite-PEO coatings consisting of anatase, rutile, TiP2O7, m-ZrO2, t-ZrO2, ZrTiO4 and Zr3(PO4)4 were formed, and ZrO2 NPs were incorporated into the coatings via both inertia and reactive modes. Both the average pore size and porosity were reduced with ZrO2 NPs addition. The adhesive strength of the PEO coatings was promoted via the addition of ZrO2 NPs. An enhancement in wear resistance was achieved for the PEO coatings with ZrO2 NPs due to the lower COF, higher microhardness and denser microstructure than that without NPs addition. The hydrophobic property was enhanced for the low surface energy modified PEO coatings with ZrO2 NPs. A significant enhancement in the corrosion resistance was achieved for the PEO coatings with the addition of ZrO2 NPs. The PEO coatings with ZrO2 NPs in 6 g/L exhibited a higher corrosion inhibition efficiency and a higher charge transfer resistance than that in other concentrations and without ZrO2 NPs addition, respectively. The enhancement in corrosion resistance for the PEO coatings with ZrO2 NPs in 6 g/L were due to the formation of corrosion-resistant phases including ZrO2 and ZrTiO4, and denser microstructure with better hydrophobic properties compared with that in other concentrations.